الهندسة المالية الإسلامية المعاصرة وإدارة مخاطرها: صيغة السلم أنموذجا - سايح، حمزة; حكيم، نشاد Nashad, Hakim (جامعة الشهيد حمه لخضر الوادي - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2021)
تهدف هذه الدراسة إلى إبراز وتوضيح أهمية صيغة السلم في تنمية اقتصاد الدول الإسلامية من جهة وتوضيح إدارة المخاطر التي تعتريها أثناء فترة التمويل من جهة أخرى كمنتج من منتجات الهندسة المالية الإسلامية. وقد توصلت الدراسة إلى أن عقد السلم يعتبر أداة تمويل شرعية ذات كفاءة عالية في الاقتصاد الإسلامي، وهو من العقود الإسلامية التي تساهم في التنمية المستدامة من جهة، ومن جهة أخرى يمثل أكثر الصيغ التمويلية الإسلامية تعرضاً للمخاطر، أبرزها المخاطر التشغيلية، المخاطر الأخلاقية المخاطر السوقية، المخاطر الائتمانية، والتي يمكن مواجهتها بعدة طرق أهمها سياسة تنويع وتوزيع المخاطر.
The formula of El Salam is one of the important forms of Islamic conversion of Islamic finance that contribute to the development of the economy of Islamic countries. The present study aims to clarify the importance of the ladder formula and clarify the risk management encountered during the financing period as a product of Islamic financial engineering products. The study also concluded that the El Salam contract is one of the Islamic contracts that contribute to the development of many economic sectors, as it fulfills the plans of continuous development and provides good opportunities for marketing agricultural and industrial products and helps to provide the necessary funding and achieve flexibility and capacity in the use of Islamic banks Any other formula, where the risks related to commodity price fluctuations have been addressed because this contract has the advantage of the seller to use the capital in any of his needs without any interference or condition from the buyer and therefore El Salam formula is a legitimate financing tool with high efficiency in the Islamic economy.
Keywords: المصارف الإسلامية -- الهندسة المالية -- المخاطر المالية -- إدارة المخاطر